A benzothiazolium-based fluorescent probe with ideal pKa for mitochondrial pH imaging and cancer cell differentiation. Issue 46 (30th October 2020) - Lin, Bo; Fan, Li; Zhou, Ying; Ge, Jinyin; Wang, Xueli; Dong, Chuan; Shuang, Shaomin; Wong, Man Shing
Abstract : A benzothiazolium-based fluorescent pH probe HTBT2 with an ideal p K a of 8.04 ± 0.02 for imaging mitochondrial pH in living cells. Abstract : A mitochondrial pH sensing fluorescent probe namely 2-(2-(6-hydroxynaphthalen-2-yl)vinyl)-3-(6-(triphenyl-phosphonio)hexyl)benzothiazol-3-ium bromide (HTBT2 ) was designed and facilely synthesized via the Knoevenagel condensation reaction. HTBT2 displayed a linear fluorescence enhancement at 612 nm in response to pH changes between 8.70 and 7.20. The p K a value was determined to be 8.04 ± 0.02, which might be ideal for mitochondrial pH (pHmito ∼8.0) detection. HTBT2 also exhibited a remarkable large Stokes shift of 176 nm, which could diminish the interference of excitation light. The results of live cell imaging studies suggested that HTBT2 showed excellent targeting ability for mitochondria. Importantly, it was successfully applied to visualize mitochondrial pH changes in live cells and differentiate the pHmito difference between cancer cell lines and normal cell lines. Our results consistently supported that HTBT2 held practical promise for the investigation of physiological processes related to pHmito changes and clinical potential for cancer cell differentiation.